Silicon-based materials as high capacity anodes for next generation lithium ion batteries - Liang, Bo; Liu, Yanping; Xu, Yunhua (Journal of power sources, 2014)
Silicon (Si)-based materials have the highest capacity among the investigated anode materials and have been recognized as one of the most promising materials for lithium-ion batteries. However, it is still a significant challenge to obtain good performance for practical applications due to the huge volume change during the electrochemical process. To date, the most successful strategy is to introduce other components into Si to form composite or alloy materials. In this review, the recent progress in Si-based materials utilized in lithium-ion batteries is reviewed in terms of composite systems, nano-structure designs, material synthesis methods, and electrochemical performances. The merits and disadvantages of different Si-based materials, the understanding of the mechanisms behind the performance enhancement as well as the challenges faced in Si anodes are also discussed. We are trying to present a full scope of the Si-based materials, and help understand and design future structures of Si anodes in lithium-ion batteries. •The paper reviewed the merits of silicon-based anodes in lithium ion batteries.•The mechanisms were discussed from in-situ TEM and first-principles simulation.•The challenges faced in silicon-based anodes were analyzed and forecast.